RNA processing bodies are disassembled during Old World alphavirus infection. (16th August 2019) - Liu, Lifeng; Weiss, Eva; Panas, Marc D.; Götte, Benjamin; Sellberg, Stina; Thaa, Bastian; McInerney, Gerald M.
Abstract : RNA processing bodies (P-bodies) are non-membranous cytoplasmic aggregates of mRNA and proteins involved in mRNA decay and translation repression. P-bodies actively respond to environmental stresses, associated with another type of RNA granules, known as stress granules (SGs). Alphaviruses were previously shown to block SG induction at late stages of infection, which is important for efficient viral growth. In this study, we found that P-bodies were disassembled or reduced in number very early in infection with Semliki Forest virus (SFV) or chikungunya virus (CHIKV) in a panel of cell lines. Similar to SGs, reinduction of P-bodies by a second stress (sodium arsenite) was also blocked in infected cells. The disassembly of P-bodies still occurred in non-phosphorylatable eIF2α mouse embryonal fibroblasts (MEFs) that are impaired in SG assembly. Studies of translation status by ribopuromycylation showed that P-body disassembly is independent of host translation shutoff, which requires the phosphorylation of eIF2α in the SFV- or CHIKV-infected cells. Labelling of newly synthesized RNA with bromo-UTP showed that host transcription shutoff correlated with P-body disassembly at the same early stage (3–4 h) after infection. However, inhibition of global transcription with actinomycin D (ActD) failed to disassemble P-bodies as effectively as the viruses did. Interestingly, blocking nuclear import with importazole led to an efficient P-bodies loss. Our data reveal that P-bodies are disassembled independently from SG formation at early stages of Old World alphavirus infection and that nuclear import is involved in the dynamic of P-bodies.